A Campus-Wide Community-Engaged Learning Study: Insights and Future Directions - Lund, Darren E.; Bragg, Bronwyn (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
The authors undertook a campus-wide scan of community-engaged learning (CEL) initiatives at a large University. With collaboration from staff and leadership of the campus Centre For Community-Engaged Learning, the researchers designed an open-ended qualitative interview and questionnaire for senior administrators and faculty leaders across all local undergraduate faculties. Guiding questions for this project included: How do the various faculties and schools within the university define their relationship with community? What activities are considered CEL? How do students engage in these activities? What are the benefits of engaging with community? From these came specific interview questions that were administered to senior administration from each faculty, and further interviews were sought with identified faculty leaders. Findings are listed by faculty, with examples and definitions, and a concluding section offers insights and discussion around strategies to strengthen and enhance CEL.